Characteristics of Chronic Kidney Disease Patient Undergoing Regular Hemodialysis with Tunneled Cuffed Catheter Dialysis Access - Noel Matthew Imaniku Sihombing; Bayu Rusfandi Nasution (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2025)
Background: Chronic kidney disease (CKD) is one of the leading contributors to morbidity and mortality rates worldwide, where end-stage patients require dialysis. Dialysis requires access, and tunneled cuffed catheters (TCCs) are considered a viable option. Objective: This study aims to describe the characteristics of the CKD patients with TCCs dialysis access at Rasyida Kidney Hospital. Methods: This descriptive study with a cross-sectional design was conducted based on patients' medical records. Total sampling was used as the sampling technique. Results: A total of 96 patients with TCC dialysis access were identified at Rasyida Kidney Hospital from January 2021 to 2024. Most patients were aged 61-75 years (39.6%), female (63.7%), and had hypertension as a comorbidity (53.8%). Additionally, 67% had a history of non-tunneled cuffed catheter access, 70.3% had the right internal jugular vein as the insertion site, and 53.8% had the indication of failed AV fistula. The duration of TCC use was more than 12 months for 65.9% of patients, and catheter thrombosis occurred in 13.2% of cases. Conclusion: The characteristics of CKD patients with TCC dialysis access at Rasyida Kidney Hospital in Medan include individuals aged 61-75 years, female, with a history of hypertension and non-tunneled cuffed catheter access, an insertion site at the right internal jugular vein, failed AV fistula as the primary indication, catheter usage for more than 12 months, and the most occurred complication is catheter thrombosis.